Logistics Business Model Strategies in Facing Changes in Big Data and Blockchain Technology: A Business Model Canvas Approach - Natalie Septiani; Alice Angelina Bitsy; Oscar Jayanagara (Blockchain Frontier Technology, 2024)
Currently, the world is undergoing a transformation towards the era of digitization and automation, which serves as a key element in business competition strategies, including in the logistics sector. The use of data for organizational decision-making has become an integral part of digitization and automation. Big Data and Blockchain technologies are now being applied in various business sectors to enhance the efficiency of business processes and impact business models, creating new transformations that align with global business developments. These changes are analyzed both internally and externally using the Business Model Canvas (BMC). A SWOT analysis of the changes in the business model is necessary to provide a detailed depiction of the new business processes. The results of the analysis indicate that: first, technological advancements, especially in Big Data and Blockchain, continue to disrupt businesses to improve optimal performance; second, the implementation of Big Data and Blockchain results in both internal and external changes related to intra- and inter-organizational relationships; third, a SWOT analysis can detail the advantages of Big Data and Blockchain technologies in the business sector, particularly in logistics.